2020
DOI: 10.1002/fsn3.1503
|View full text |Cite
|
Sign up to set email alerts
|

Microbial quality and formation of biogenic amines in the meat and edible offal of Camelus dromedaries with a protection trial using gingerol and nisin

Abstract: This study aimed firstly at the investigation of the microbial status of the camel meat and edible offal including liver, kidneys, lungs, rumen, and duodenum distributed at local markets of Egypt. Total plate count, total psychrophilic counts, total Enterobacteriaceae count, the most probable number of coliforms, and total mold counts were monitored at the collected samples. The produced biogenic amines (BA) in the camel meat and offal were further estimated. An experimental trial to investigate the antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Gharsallaoui et al [ 19 ] already found that nisin has strong antimicrobial effects on meat and meat products when used alone or in combination with other antimicrobials. The same findings were pointed out by Tang et al [ 6 ] who found that nisin combined with gingerol significantly reduced microbial growth and subsequent formation of biogenic amines in the meat and edible offal of camel. The highest dose of laper .OLE (1000 ppm) combined with nisin (25 ppm) kept TPM counts below 5 log 10 cfu/g values, even at the end of storage (30 days).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Gharsallaoui et al [ 19 ] already found that nisin has strong antimicrobial effects on meat and meat products when used alone or in combination with other antimicrobials. The same findings were pointed out by Tang et al [ 6 ] who found that nisin combined with gingerol significantly reduced microbial growth and subsequent formation of biogenic amines in the meat and edible offal of camel. The highest dose of laper .OLE (1000 ppm) combined with nisin (25 ppm) kept TPM counts below 5 log 10 cfu/g values, even at the end of storage (30 days).…”
Section: Resultssupporting
confidence: 83%
“…The promotion and preservation of the quality characteristics of camel meat constitute a major challenge for breeders, butchers, and, possibly, manufacturers located in arid regions. In recent years, several studies have been carried out on the use of different methods (biopreservation, modified atmosphere packaging (MAP) and active packaging) to extend the shelf-life of meat and meat products of several species such as camel, beef, and pork [ 4 , 5 , 6 ]. The search for new alternatives to maintain the quality stability of camel meat has become necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, significant positive correlations were observed between TBAs and TPC in the different fish species, particularly in the Tilapia, Herrings, and Sardine (Table 3). Similarly, Positive correlations between microbial counts and the formation of BAs were reported in the fish ( Visciano et al., 2012 ) , camel meat ( Tang et al., 2020 ) , and cheese ( Ma et al., 2020 ) . These results highly suggest that the initial microbial counts, storage conditions, and the kind of the fish determine the extent of the formation of BAs in the raw fish.…”
Section: Resultsmentioning
confidence: 73%
“…Meat and dairy products including mince, sausage, luncheon, basterma, milk, cheese, yoghurt, and dried milk powder are preferred by a large section of the population because of their specific aroma and flavor, high nutritive values, and their easy preparation. Hygienic measures adopted during handling and processing of such products affect their initial microbiological load and subsequently affect their safety, and keeping (Tang et al, 2020). Asa major task for the food hygiene and food microbiology sectors is to confirm their microbial status of the retailed meat, milk and their and meat and dairy products.…”
Section: Discussionmentioning
confidence: 99%